Development of an E-Module Based on the Islamic Integrated CORE Model for MTs Students on Systems of Linear Equations in Two Variables - Sri Windar Ningsih; Ramon Muhandaz (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The use of electronic teaching materials in the current technological era is still not optimal, even though digital media can expand access and the scope of learning, thereby making the learning process no longer limited by time and place. This research aims to develop an e-module based on the Islamic integrated CORE model that is valid, practical, and effective on the material Systems of Linear Equations in Two Variables (SPLDV). The research method used is Research and Development (R&D) with the ADDIE model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were class VII students at MTs Al-Qasimiyah Sorek Satu, while the research object was an e-module based on the Islamic integrated CORE model. Research data includes quantitative data in the form of expert validation scores, practicality scores, and post-test results, as well as qualitative data in the form of comments, validator suggestions, and student responses. The results of validity tests by material experts, Islamic experts, and learning technology experts show that the e-module is in the very valid category. The students' practicality test also indicates that the e-module falls into the practical learning category. The effectiveness test was analyzed using the Mann–Whitney U test, which was strengthened by the Z test. The results showed a significant difference in learning outcomes between the experimental and control classes, with the experimental class achieving a higher average post-test score. These findings show that e-modules are not only valid and practical, but also effective in improving student learning outcomes. Thus, e-modules based on the CORE model, integrated with Islam in SPLDV material, are suitable as alternative teaching materials for mathematics learning at the MTs level and have the potential to support a learning process that is more interactive, meaningful, and in line with Islamic values.